Analisis Sentimen Terhadap Bullying Di Indonesia Pada Twitter Menggunakan Naïve Bayes dan SVM - AlHakim, Abdu Malik; Leonardo D.P, Harun; Putri, Alifia Nursyahrani (Jurnal Riset Informatika dan Teknologi Informasi, 2025)
Bullying has become a serious social problem in Indonesia. In the past few years, bullying cases are increasing, especially among children and adolescents. Bullying can occur anywhere, including at home, work, community, social media, and school, but it is most common in educational settings. Twitter or "X" is the most used social media in Indonesia, often a place for people to express their opinions on bullying. This research aims to analyze sentiment towards bullying in Indonesia through comments or tweets collected from Twitter using Naïve Bayes and Support Vector Machine (SVM) methods. From the analysis of 330 tweets, the Naïve Bayes method showed an accuracy of 77.27%, while the SVM method showed an accuracy of 72.72%.